Statistical Analytic Tool for Dimensionalities in Big Data: The role of Hierarchical Cluster Analysis - Mbukwa, Justine N.; Tabita, G Neeha; Anjaneyulu, GVSR; Rajasekharam, OV (Research India Publications, 2024)
Article published by Research India Publications in the International Journal of Statistics and Systems Volume 11, Number 1 (2016), pp. 19-26